2020
DOI: 10.14808/sci.plena.2020.090201
|View full text |Cite
|
Sign up to set email alerts
|

Effects of organic compost, gypsum, and topdress sulfur rates on bioactive compounds and physicochemical characteristics of collard greens

Abstract: Estudou-se a utilização do enxofre, gesso e composto orgânico sobre compostos bioativos e características físico-químicas de couve-de-folha. Foram avaliados doze tratamentos, em esquema de parcelas subdivididas, sendo três tipos de preparo de solo as parcelas, e quatro doses de enxofre em cobertura as subparcelas. O preparo de solo foi realizado de três modos: incorporação pré-plantio de composto orgânico; gesso agrícola e composto orgânico + gesso agrícola. As doses de enxofre para adubação em cobertura foram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…The "Spad" index can be indicative of N deficiency and helps in the management of nitrogen fertilization of some vegetables (Mógor et al, 2013;Nasser et al, 2020). Studies with increasing applications of nitrogen and organic fertilizers in zucchini (Ferreira et al, 2006) and tomatoes (Porto et al, 2011) found increases in chlorophyll contents and "Spad" index values, which was not observed in the present study when comparing the control with the treatments that received castor bean cake or hoof and horn powder.…”
Section: Resultscontrasting
confidence: 80%
See 1 more Smart Citation
“…The "Spad" index can be indicative of N deficiency and helps in the management of nitrogen fertilization of some vegetables (Mógor et al, 2013;Nasser et al, 2020). Studies with increasing applications of nitrogen and organic fertilizers in zucchini (Ferreira et al, 2006) and tomatoes (Porto et al, 2011) found increases in chlorophyll contents and "Spad" index values, which was not observed in the present study when comparing the control with the treatments that received castor bean cake or hoof and horn powder.…”
Section: Resultscontrasting
confidence: 80%
“…No researches were found describing the accumulation of nutrients in parsley, which prevents comparison with other authors. However, it is observed that K is the most accumulated nutrient, followed by N, what is also observed in different leaf vegetables, such as endive (Lanna et al, 2017), kale (Nasser et al, 2020) and cabbage (Corrêa et al, 2013), as well as in roots such as carrots (Colombari et al, 2018) and beets (Cardoso et al, 2017), and in fruit vegetables such as zucchini (Araújo et al, 2015) and watermelon (Grangeiro & Cecílio Filho, 2005).…”
Section: Luís Et Al (2023)mentioning
confidence: 95%
“…However, too much sulfur or gypsum can also have negative effects on the compost quality, such as reducing microbial activity, increasing the T Environment, Biodiversity & Soil Security (EBSS) http://jenvbs.journals.ekb.eg salinity, and inhibiting plant growth. Bello, S. K., et al (2021) Therefore, it is important to monitor the pH of the compost and adjust the amount of sulfur or gypsum accordingly (Day et al, 2019;Nasser et al, 2020). Another factor that can affect the compost properties is the treatment applied to the corn stalks compost after the composting process.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various organic fertilizers with the potential to be used in top dressing fertilization of vegetables, there are hoof and horn powder and castor bean cake (Cardoso et al, 2020;Lanna et al, 2020;Almeida et al, 2021;Hounmenou et al, 2021;Nordi et al, 2022). Castor bean cake, a residue from castor bean processing, is an important source of nitrogen, with phosphorus, potassium, and micronutrients in smaller quantities (Nasser et al, 2020). Hoof and horn powder are a residue from the processing and slaughter of cattle, rich in nitrogen (Nordi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%